The relationship between the philosophy of scientific knowledge and curriculum in Molecular Bioscience teaching at a tertiary learning institution - Legg-E’Silva, Derryn Audrey (My University, 2018)
The relationship between teacher beliefs about the nature of science and scientific knowledge and pedagogical practice has been well studied. However, this has mainly been for teachers at school level. This study examined this relationship, in lecturers, at a university level where a single course is taught by multiple lecturers, each with their own beliefs and teaching practices. Anecdotal evidence suggests that science students are receiving mixed messages about the nature of science and scientific knowledge, these are contradictory to what they should be learning in order to think and reason like true scientists. Data was collected from four lecturers who lecture across the same Molecular Biosciences course in the form of interviews, classroom observations and text analyses in order to ascertain the relationship between the beliefs, practices and assessment approaches of each lecturer. The findings indicate that coherence exists between lecturers ’ beliefs and practices and is in agreement with previous research. However, this coherence does not occur between the lecturers. One lecturer was found to be positivist, two lecturers transitional and one lecturer reform-based in their beliefs and teaching approaches. An interesting finding with regards to assessment was revealed and provided an explanation for mixed messages science students may be receiving regarding the nature of science and scientific knowledge. It can therefore be concluded that lecturers’ beliefs about the nature of science and scientific knowledge are mirrored in their practices. This information may be useful for lecturer and teacher training and can be included in university and school discussions about views of teaching and assessment.
A research report submitted to the Faculty of Science, University of the Witwatersrand, in partial fulfilment of the requirements for the degree of Masters in Science Education. Johannesburg, 2017.
Keywords: Educational change; Teaching; Science--Study and teaching; Education--Research